Incidence of cervical lymph node metastasis and its association with outcomes in patients with adenoid cystic carcinoma. An international collaborative study. Issue 7 (24th July 2014) - Amit, Moran; Binenbaum, Yoav; Sharma, Kanika; Ramer, Naomi; Ramer, Ilana; Agbetoba, Abib; Glick, Joelle; Yang, Xinjie; Lei, Delin; Bjørndal, Kristine; Godballe, Christian; Mücke, Thomas; et al.
Abstract Background The patterns of regional metastasis in adenoid cystic carcinoma (ACC) of the head and neck and its association with outcome is not established. Methods We conducted a retrospective multicentered multivariate analysis of 270 patients who underwent neck dissection. Results The incidence rate of neck metastases was 29%. The rate observed in the oral cavity is 37%, and in the major salivary glands is 19% (p = .001). The rate of occult nodal metastases was 17%. Overall 5‐year survival rates were 44% in patients undergoing therapeutic neck dissections, and 65% and 73% among those undergoing elective neck dissections, with and without nodal metastases, respectively (p = .017). Multivariate analysis revealed that the primary site, nodal classification, and margin status were independent predictors of survival. Conclusion Our findings support the consideration of elective neck treatment in patients with ACC of the oral cavity. © 2014 Wiley Periodicals, Inc. Head Neck 37: 1032–1037, 2015